2017
DOI: 10.1177/1687814016686891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of squeeze force on static behavior of riveted lap joints

Abstract: To study the effects of the squeeze force used in the rivet installing process on structural behavior of the riveted lap joints, three-stage finite element simulation and workshop experiment of single-row countersunk riveted lap joints were implemented. Force-displacement curves and explicit configuration after various processes were obtained from both methods. Additionally, stress/strain fields were obtained from finite element analysis, and strain values at specific positions were measured by micro strain ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This linear relationship is effective for predicting the fatigue properties of joints. Zhou et al [35] found that clamping the interference-fitted joint exhibits higher fatigue lives than that of clamping of the cold-expanded and interferencefitted joint at low stress levels, while at high stress levels, the results are opposite, which explains exactly the results obtained by Huan et al [24], who concluded that the influence of interference-fit on fatigue properties of joints is closely related to the stress level. Skorupa et al [38] concluded that the interference-fit between the rivet and the hole can effectively compensate for the notch effect under the axial loadings to improve fatigue properties of riveted joints.…”
Section: Interference-fitmentioning
confidence: 65%
See 3 more Smart Citations
“…This linear relationship is effective for predicting the fatigue properties of joints. Zhou et al [35] found that clamping the interference-fitted joint exhibits higher fatigue lives than that of clamping of the cold-expanded and interferencefitted joint at low stress levels, while at high stress levels, the results are opposite, which explains exactly the results obtained by Huan et al [24], who concluded that the influence of interference-fit on fatigue properties of joints is closely related to the stress level. Skorupa et al [38] concluded that the interference-fit between the rivet and the hole can effectively compensate for the notch effect under the axial loadings to improve fatigue properties of riveted joints.…”
Section: Interference-fitmentioning
confidence: 65%
“…Most of studies have focused on the influence of squeeze force on residual stress/strain distribution and SB stresses after rivet installation. Huan et al [24] conducted experiments of single-row countersunk riveted lap joints to investigate the squeeze force effect on static behaviour of the riveted lap joints. The joint stiffness became nonlinearly smaller with the gradually increased tensile load, while the effect of squeeze force on joint stiffness was not significant.…”
Section: Fatigue Failurementioning
confidence: 99%
See 2 more Smart Citations
“…It was found that if the rivet length and diameter increase, the amount of squeeze force needed to drive a rivet increases. [7] experimentally evaluated the structural behaviour of riveted lap joints with squeeze force. The study comprised of static strength experiments and FE analysis.…”
Section: Literature Reviewmentioning
confidence: 99%